Auditoría operativa y su incidencia en el cumplimiento en el área de caja del banco de Machala sucursal Quevedo. año 2023. - Morante Mendoza, Shirley Johanna (2024)
The following investigation raised a problem of vital importance as the operational audit affects the level of compliance in the cash area in addition to how the level of compliance with the current rules and regulations applicable to the cash area is established, thus this investigation had The objective is to identify the level of compliance with the personnel's operational processes, in addition to measuring the level of effectiveness and efficiency in compliance with the operational processes through management indicators. The investigative work was carried out at the Bank of Machala with a branch in the Quevedo canton, which is why the population subject to study consisted of six people designated in the aforementioned area, four of whom, called Receivers - Payers, were evaluated by means of From a survey, an interview related to operational processes was directed to the cash manager and the assessment of administrative procedures was carried out to the Deputy Manager of the entity. The study contained an exploratory and descriptive type of research in addition to an inductive, deductive and analytical method. Together, an observation, interview and survey guide was carried out to obtain the necessary data to later be tabulated, graphed and analyzed and finally show the conclusions and recommendations relevant to the investigation.